Ligand‐Promoted RhI‐Catalyzed C2‐Selective C−H Alkenylation and Polyenylation of Imidazoles with Alkenyl Carboxylic Acids. Issue 36 (19th May 2022) - Zhao, Haoqiang; Luo, Zhenli; Yang, Ji; Li, Bohan; Han, Jiahong; Xu, Lijin; Lai, Wenzhen; Walsh, Patrick J.
Abstract: The first Rh I ‐catalyzed, directed decarbonylative C2−H alkenylation of imidazoles with readily available alkenyl carboxylic acids is reported. The reaction proceeds in a highly regio‐ and stereoselective manner, providing efficient access to C2‐alkenylated imidazoles that are generally inaccessible by known C−H alkenylation methods. This transformation accommodates a wide range of alkenyl carboxylic acids, including challenging conjugated polyene carboxylic acids, and diversely decorated imidazoles with high functional group compatibility. The presence of a removable pyrimidine directing group and the use of a bidentate phosphine ligand are pivotal to the success of the catalytic reaction. This process is also suitable for benzimidazoles. Importantly, the scalability and diversification of the products highlight the potential of this protocol in practical applications. Detailed experimental and computational studies provide important insights into the underlying reaction mechanism. Abstract : A Rh I ‐catalyzed C2−H alkenylation of imidazoles with alkenyl carboxylic acids with highly regio‐ and stereoselectivity is reported. This protocol merges C−H bond functionalization and the decarbonylation of carboxylic acids, accommodates a wide range of substrates with good compatibility of functional groups, and can be easily scaled.